NON-STATE ACTOR IN CONFLICT TRANSFORMATION: MULTICULTURAL EDUCATION OF MA DAARUL ULUUM PUI MAJALENGKA TOWARDS ETHNO-RELIGION CONFLICT IN SOUTHERN THAILAND - Zabieb Nu’aim Ridwan; Sugito Sugito (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
The conflict between the Malay Muslim and the Thailand government in Southern Thailand has become one of the ethno-religion conflicts that effects the security of the Southeast Asian region. Various actors, both local and international, have attempted to broker peace between the parties in the conflict. Based on the conflict transformation theory, this study aims to discover the role of MA Daarul Uluum PUI Majalengka as a non-state actor in promoting peace through efforts of conflict transformation in the Southern Thailand ethno-religion conflict. The research method used is qualitative type research with descriptive analysis technique, through primary and secondary type data management. Primary data was obtained from interview and secondary data was obtained from written sources that support the study. This research shows there is an effort made by MA Daarul Uluum PUI Majalengka to conduct peace education through a student and teacher exchange scheme with several schools in Thailand that have Buddhist identity backgrounds in order to grow tolerance between ethnicities and religions in Thailand.